Does previous open nephrolithotomy affect the efficacy and safety of tubeless percutaneous nephrolithotomy? - Lojanapiwat B. (2017)
Introduction: Tubeless percutaneous nephrolithotomy (PCNL) in selected patients is effective and results in less postoperative discomfort without increasing complications. The challenges of PCNL in patients who had a history of open nephrolithotomy are decreased kidney mobility due to scarring around the kidney and distortion of the renal collecting system, conditions that may cause difficulty of tract access and increase retained stone and hemorrhagic complications. We compared the efficacy and safety of the tubeless versus the standard PCNL in patients who had undergone previous open nephrolithotomy. Patients and Methods: Percutaneous nephrolithotomy (PCNL) was performed in 104 patients who had a history of previous open nephrolithotomy, of which 45 received tubeless PCNL (group I) and 59 received standard PCNL with routine postoperative nephrostomy tubes (group II). All patients had only one percutaneous renal access and showed no significant bleeding, extravasation or residual stone. Of group I, PCNL was done by the standard technique with only placement of a postoperative external ureteral catheter for 48 h. The success rate, operative time, hospital stay and complications were compared between the two groups. Results: Patient's demographic data were not different between both groups. Infundibular stenosis and ureteropelvic junction obstruction were found in 2 and 4 cases of groups I and II, respectively. The success rates, operative time and complication rates were not significantly different between both groups. Hospital stay was 3.53 and 5.39 days for groups I and II, respectively, which was significantly different. Average analgesic (meperidine) usage was significantly less in the tubeless group (39 ± 35 mg for group I and 75 ± 32 mg for group II). Conclusion: Tubeless PCNL in selected patients with previous open nephrolithotomy has a safe and effective advantage compared to standard PCNL as indicated by a decrease in length of hospital stay and analgesic usage. Copyright © 2010 S. Karger AG.